Is obesity a predisposing factor for free flap failure and complications? Comparison between breast and nonbreast reconstruction: Systematic review and meta-analysis - Shin, Jin Yong (Medicine (Baltimore), 2016)
Obesity is a risk factor for postoperative morbidity in breast reconstruction. Although existing studies about nonbreast reconstruction are limited, previous research has demonstrated that obesity is not an important factor in poor outcomes in nonbreast reconstruction. Our study evaluates the effects of obesity on postoperative morbidity in nonbreast reconstruction in comparison to breast reconstruction. A systematic literature review and meta-analysis was performed using Medline, EMBASE, and Cochrane databases. Obesity was extracted for predictor variables and partial, total loss of flap, and complication were extracted for outcome variables. Subgroup analyses were performed according to reconstruction site. The Newcastle-Ottawa scale (NOS) was used to assess the quality of the studies, and the Cochrane risk of bias tool was used. Publication bias was evaluated using funnel plots. The search strategy identified 944 publications. After screening, 19 articles were selected for review. Partial flap loss, total flap loss, and complications in breast reconstruction occurred significantly more often in obese patients in comparison to nonobese patients (OR = 2.479, P = 0.021 for partial loss, OR = 3.083, P = 0.002 for total loss, OR = 2.666, P = 0.001 for complications). In contrast, partial flap loss, total flap loss, and complications in nonbreast reconstruction were not significantly different in obese patients in comparison to nonobese patients (OR = 0.786, P = 0.629 for partial loss, OR = 0.960, P = 0.961 for total loss, and OR = 1.009, P = 0.536 for complications). In contrast to the relationship between obesity and poor outcomes in breast reconstruction, our study suggests the obesity is not a predisposing factor for poor outcomes in nonbreast reconstruction. Long-term studies are needed to confirm these findings.